Hubungan Antara Remunerasi Dengan Motivasi Kerja Pegawai Negeri Sipil di Rumah Sakit Umum Pusat Sanglah Denpasar - Swantara, Kadek Agus; Suprilyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2018)
ABSTRACT In this study were obtained throught a sample deployment with total samples of 95 employees at Central Hospital of Sanglah Denpasar. The analysis result of research findings showed that remuneration variabel has positive and significant impact on the work motivation at the Central Hospital of Sanglah Denpasar with the result of R2 was 71,2%, and the remaining 28,8% was influenced by other factors. Meanwhile, if the remuneration is increased by 1%, automatically, the work motivation will increase by 1,004. Keywords: Remuneration, Work Motivation